Approximate controllability of evolution hemivariational inequalities under nonlocal conditions - Yongwei Jia (AIMS Mathematics)
This article utilizes fixed-point theory and nonsmooth analysis to study the existence and approximate controllability of mild solutions for a class of nonlinear evolution hemivariational inequalities with nonlocal conditions in Hilbert spaces. In fact, our main results encompass a broader range of related issues. Finally, we use an example to illustrate that our results are valuable.